Impacts of extreme warming in 2016–2019 on the stock of pacific cod Gadus macrocephalus (Gadidae) in the Russian waters of northwestern Bering Sea - Y. I. Zuenko; A. B. Savin; E. O. Basyuk (Известия ТИНРО, 2025)
“Heat wave” in the Bering Sea in 2016–2019 and its consequences for oceano- graphic conditions and local populations of pacific cod Gadus macrocephalus are considered. The feeding stock of cod in the northwestern part of the sea (Russian EEZ) had fluctuated previously (1965–2012) from 25 ∙ 103 to 654 ∙ 103 t, but increased up to 1329.7 ∙ 103 t in 2017. Features of the size-age structure for the cod fed in this area in the years of “heat wave” showed a prevalence of migrants from the southeastern Bering Sea. Such active migrations of cod were conditioned by extreme heating of the water and destruction of the cold water pool at the shelf bottom caused by strengthening of warm currents that enforced the traditional migration from the south-east to the north-west and opened a new route — northward from the southeastern Bering Sea, across the shelf of Alaska to the coasts of Chukotka Peninsula or even to the Bering Strait and Chukchi Sea. Both routes coincided with the streams of the Bering Slope Current and Alaska Coastal Current, which encircled the cold water pool from two sides and destroyed this water mass. A hypothesis is proposed that the migrations were driven by northward transport of krill Thysanoessa inermis by these currents from the area of their reproduction at the continental slope accompanied by feeding migrations of their main grazer — walleye pollock. The study results allow to optimize the cod fishery in the Bering Sea for comprehensive utilization of this strongly fluctuating stock.